An Assessment of BHLHE40 Transcription Factor Level and its Target Cytokines in Patients with Rheumatoid Arthritis - Ghotloo, Somayeh; Zamani, Batol; Osatadian, Amir-Reza; Marzhoseyni, Zeynab (Recent Advances in Inflammation & Allergy Drug Discovery, 2025)
<span class=
Keywords: BHLHE40